2003
DOI: 10.1063/1.1590413
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of selective quantum well intermixing in 1.3 μm GaInNAs/GaAs structures

Abstract: Rapid thermal annealing combined with SiO 2 caps deposited on the surface of samples by different techniques is used to selectively disorder 1.3 m GaInNAs/GaAs multiquantum wells which have been preannealed in situ to the stage of blueshift saturation. After thermal annealing under specific conditions, a shift in band gap of over 170 meV has been obtained in sputtered SiO 2 -capped samples, while uncapped and plasma enhanced chemical vapor deposited SiO 2 -capped samples demonstrated a negligible shift. Quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…We believe that these spacer layers at the interfaces affect the PL properties by means of a reduction in the defectrelated In-Ga interdiffusion of atoms between the quantum wells and the barriers, which is also observed by others. [15][16][17] …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We believe that these spacer layers at the interfaces affect the PL properties by means of a reduction in the defectrelated In-Ga interdiffusion of atoms between the quantum wells and the barriers, which is also observed by others. [15][16][17] …”
Section: Discussionmentioning
confidence: 98%
“…Effects on the PL caused by the introduction of the spacer layers placed in between the quantum wells and barriers are most influential at these higher thermal energies in preventing the In and Ga from interdiffusing between the quantum wells and barriers. Macaluso et al 15 and Sun et al 16,17 have also observed this In-Ga interdiffusion to be exacerbated in annealed GaInNAs quantum-well structures that were capped with SiO 2 using an ion sputtering process, Rapid Thermal Annealing Effects on the Photoluminescence Properties of Molecular Beam Epitaxy-Grown GaIn(N)As Quantum Wells with Ga(N)As Spacers and Barriers 857 which generated increased point defects in their sample. We believe that the ions from their sputtering process are comparable to the ions generated from our N-plasma source, leading to plasmarelated crystal damage in our samples.…”
Section: Section Iii: Quantum Wells With 32% In and Barriers With 1% mentioning
confidence: 90%
“…The use of inter-diffusion of quantum wells (QWs) is an emerging technology that is significant for fabricating semiconductor lasers since it improves devices' optical and electrical properties [16]. Selective inter-diffusion is achievable by obscuring into the QW wafer's desired regions.…”
Section: Introductionmentioning
confidence: 99%
“…Selective inter-diffusion is achievable by obscuring into the QW wafer's desired regions. Since the 1980s, there have been extensive investigations regarding inter-diffusion [16,17]. It comprises disordering or intermixing of heterostructures that are quantum-confined like QWs and quantum dots (QDs).…”
Section: Introductionmentioning
confidence: 99%
“…17,20 Strong QW/barrier intermixing ͑which was mainly observed for MBE-grown samples 7,9,12 ͒ can be caused by the enhanced presence of point defects ͑which originate from the rf nitrogen plasma source used for incorporating N in MBE͒. Sun et al 21 showed the secondary ion mass spectrometry of MBE samples that intentionally introducing point defects in the material results in the interdiffusion of group-III atoms between the QWs and barriers, and hence in a blueshift of the PL signal. It is also possible that point defects promote-in addition to interdiffusion-in-plane compositional diffusion.…”
Section: Introductionmentioning
confidence: 99%